Management of Chemical Weapons Victims in Terms of Disaster Medicine Afet Tıbbı Açısından Kimyasal Silah Yaralılarının Yönetimi - Öztürk İ.; Güneren E.; MAYADAĞLI A.; ERDOĞAN Ö. (My University, 2020)
Today, as Chemical, Biological, Radiological and Nuclear (CBRN) weapons are generally used to cause terror and havoc, they are also used to bring about mass destruction and breach of the capacity. Since CBRN weapons are easily procurable, they became an untrammeled power supply in the hands of weak states. Despite all international judgments, treaties and pressures preventing production, storage and usage of chemical weapons, uncontrolled usage still has not been averted. Dual-use feature of some chemicals provides convenience in their trading permissions and their passing through customs. Because chemical detections are difficult and early warning systems are not prevalent in border crossings and customs entries, there is an increasing danger. Disregard of the agencies and institutions meant to be responsible from protecting human health and health of other species, jeopardizes the situation more. In terms of disaster medicine, management of injuries with chemical warfare agents and injured peoples require a multi-disciplinary approach, study and coordination. Unfortunately, academic studies regarding standard procedures and algorithms of rescue and health services provided to the injured peoples as from the initial contact,-especially in the case of injuries with chemical weapons-have a very limited availability. On the purpose of removing this uncertainty and remedying the current deficiency; scientists, forensic science experts, health care providers, chemists, engineers, search and rescue experts, firefighters, members of the managerial disciplines, legists, logistics specialists and experts related to the security field urgently need to determine required standard algorithms of prevention and response. In this study; the medical care processes of chlorine gas as chemical weapons wounded in Syria due to Syrian civil war are evaluated in terms of disaster medicine.
Keywords: Sosyal ve Beşeri Bilimler; Coğrafya; Mühendislik ve Teknoloji; Social Sciences and Humanities; Geography; Engineering and Technology; Mühendislik Bilişim ve Teknoloji (Eng); Temel Bilimler (Sci); Mühendislik; Yerbilimleri; Mühendislik İmalat; Mühendislik Çevre; Engineering Computing & Technology (Eng); Natural Sciences (Sci); Engineering; Geosciences; Engineering Manufacturing; Engineering Environmental; Emniyet, Risk, Güvenilirlik ve Kalite; Fizik Bilimleri; Çevre Mühendisliği; Coğrafya, Planlama ve Geliştirme; Sosyal Bilimler ve Beşeri Bilimler; Safety, Risk, Reliability and Quality; Physical Sciences; Environmental Engineering; Geography, Planning and Development; Social Sciences & Humanities; CBRN; Chemical Weapon; Disaster Medicine; Medical Care